(untitled) (Indian Journal of Animal Production and Management, 2024)
Eighteen Hampshire sows with their litters were randomly selected and divided into three groups keeping similar parities (1-4) from 4th week onwards viz. unrestricted suckling (T1), 6 hours restricted suckling (T2) and 12 hours restricted suckling (T3) groups. All the animals were reared under standard feeding and management conditions. The piglets were weaned at 8th week of age. The sows were observed for reproductive performance in the successive lactation. The average body weight loss of sows during 4th to 8th week was found to be 16.13 ± 1.98, 11.42 ± 0.71 and 7.70 ± 0.73 kg in T1, T2 and T3 groups, respectively, which differed significantly (P<0.01) among treatment groups. The average service period of sows in T1, T2 and T3 groups was 123.83 ± 13.61, 113.50 ± 6.66 and 110.17 ± 14.82 days, respectively. The average service period did not differ significantly. The service period was apparently shorter in T3 group. The average litter size at birth was 6.83 ± 0.87, 8.50 ± 0.42 and 8.67 ± 1.09 in T1, T2 and T3 groups, respectively. The average litter weight at birth was 6.82 ± 0.60, 8.97± 0.39 and 9.85 ± 1.14 kg in T1, T2 and T3 groups, respectively. There was significant (P<0.05) effect of restricted suckling on the average litter weight at birth. The average litter weight at birth was significantly higher in T3 group than that of T1 group but it did not differ significantly from T2. The present study revealed that reproductive performance of sows was improved due to restricted suckling by their piglets from 4th week onward